Attempts to Change the World: Building Assemblies in Portuguese Contemporary Theatre. The Case of Gonçalo Amorim - Coelho, Rui Pina (2022)
What presides in the arguments presented in this essay is the idea that Portuguese contemporary theatre has been creating the space and developing practices that we can envisage in the creation of assemblies implicated and interested in changing the world, pre-enacting a sphere for social discussion and debate. Thus, we would look at these attempts to change the world through the constructions of theatre assemblies in Portuguese contemporary theatre accordingly to the case of Gonçalo Amorim's Experimental Theatre from Oporto. Thus, this essay aims to present and discuss some of the creative methodologies and processes undertook in this theatre collective, namely the "discussions on stage" strategy. This specific way of creating a text/performance can be related, I believe, with what can be understood as way to manifest their world vision and their political beliefs.